1997
DOI: 10.1186/cc103
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: The use of diuretics and dopamine in acute renal failure: a systematic review of the evidence

Abstract: ObjectiveTo evaluate the impact of diuretics and dopamine for both the prevention and treatment of renal dysfunction in the acute care setting.Study identification and selectionStudies were identified via MEDLINE, and through bibliographies of primary and review articles. Articles were then screened by the author for studies addressing the use of diuretics or dopamine in the prevention and/or treatment of renal dysfunction.Data abstraction and literature appraisalFrom individual studies, data were abstracted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(4 citation statements)
references
References 52 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…In terms of potential nephroprotective effects, researchers have previously attempted to use low dose dopamine (0.5–3 µg/kg/min) to increase renal blood flow and potentially protect the kidneys from cisplatin ( Kellum, 1997 ). The results of multiple studies were conflicting, and do not currently support the use of dopamine as a nephroprotectant ( Crona et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of potential nephroprotective effects, researchers have previously attempted to use low dose dopamine (0.5–3 µg/kg/min) to increase renal blood flow and potentially protect the kidneys from cisplatin ( Kellum, 1997 ). The results of multiple studies were conflicting, and do not currently support the use of dopamine as a nephroprotectant ( Crona et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…At low doses (i.e., 3 µg/kg/min) dopamine is vasodilatory and promotes diuresis primarily through the D-1 receptor and has beneficial effects in multiple models of AKI (121). Despite this, multiple studies have consistently demonstrated that renal-dose dopamine or the dopamine agonist fenoldapam, do not influence outcome of AKI in patients despite producing diuresis (45, 254, 255, 288, 560). Similarly, atrial natriuretic peptide can produce diuresis in AKI patients but does not provide any improvement in renal function or recovery (305).…”
Section: Pathophysiology Hemodynamics and Inflammationmentioning
confidence: 99%
“…Diuretics have also been used in patients with oliguric AKI to improve urine output, which may decrease the concentration of toxins and improve clearance of solute and medications. It should be noted, however, that the increase in urine flow provided by diuretic therapy does not reflect an improvement in GFR, nor has it been demonstrated to prevent or facilitate recovery from acute tubular necrosis [177]. In addition, children with AKI may deteriorate further with diuresis, particularly patients with prerenal or radiocontrast-induced AKI [178].…”
Section: Diagnosis Treatment and Outcomementioning
confidence: 99%